A SENSITIVE AND A SIMPLE RP-HPLC METHOD DEVELOPMENT AND VERIFICATION FOR THE QUANTITATIVE ESTIMATION OF CHOLECALCIFEROLIN TABLETS - SUBHASHINI, K.; NAIDU, U. TRIVIKRAM; KUMAR, A. ASHOK; VOOTURI, RAJESH; KUMAR, N. VENU (International Journal of Current Pharmaceutical Research, 2023)
Objective: To develop a sensitive, simple, accurate, precise and linear Reverse Phase High-Performance Liquid Chromatographic (RP-HPLC) method and verify for the quantitative estimation (Assay) of Cholecalciferol in tablets. Methods: The optimized method uses a reverse phase column, Waters X-Bridge C8 (150 X 4.6 mm; 3.5μ), a mobile phase of Methanol: Acetonitrile: HPLC grade water/Milli-Q water in the proportion of 60:30:10 v/v/v, flow rate of 0.8 ml/min, injection volume of 100 µl, and detection wavelength of 265 nm using a UV/PDA detector. Results: The developed method gave Cholecalciferol eluting at about 9 min. Cholecalciferol exhibited linearity in the range 0.058-0.466 μg/ml. The precision is exemplified by a relative standard deviation of 1.40%. Percentage of individual recovery was found to be in the range of 97.0 and 103.0 during accuracy studies. Conclusion: A sensitive, simple, accurate, precise and linear RP-HPLC method was developed and verified for the quantitative estimation (Assay) of Cholecalciferol in tablets and hence this method can be explored for the analysis of Cholecalciferol in tablets/various dosage forms in various pharmaceutical industries.